Crystal geometry of defectless three component L21 superstructure for antiphase boundaries specification in Heusler type compounds - Схарапов E. A.; Корзникова E. A.; Семенов A. S.; Дмитриев S. V. (Materials. Technologies. Design, 2020)
Among the wide variety of ternary alloys, a special place is occupied by the group of Heusler compounds which are usually defined as ternary intermetallic compounds formed upon stoichiometric composition of A2BC with L21 structure type. These materials demonstrate a set of unusual phenomena such as, for instance barocalorimetric, thermomagnetic effects, Peltier and Seebeck effects, shape memory effects and some others. Due to these unique properties Heusler compounds can be referred as a relevant object of investigation in modern material science community. It is well known, that in most cases properties of the material and its behaviour upon the modification of external conditions is defined by the defects present in the crystal lattice. The number of possible defect types grows upon the increase of the number of components and decrease of the crystal lattice symmetry class. In ordering alloys with complex internal structure and rigorous stoichiometry so called antiphase boundaries play a great role in the formation of the complex of properties of the material. In order to develop the classification of this defect type in frames of their geometrical and energetical characteristics for a definite superstructure one should carefully describe the crystallogeometry of the alloy considering the interactions in closest coordination spheres. The present work addresses the geometrical analysis of the Heusler compound type structure with A2BC stoichiometry and L21 superstructure.